Occurrence of Antibiotics and Antibiotic-Resistant Bacteria in Landfill Sites in Kumasi, Ghana. (4th July 2019) - Borquaye, Lawrence Sheringham; Ekuadzi, Edmund; Darko, Godfred; Ahor, Hubert Senanu; Nsiah, Sarah Twumwah; Lartey, Jemima Asi; Mutala, Abdul-Hakim; Boamah, Vivian Etsiapa; Woode, Eric
Abstract : The incidence of antimicrobial resistance among microbial communities is a major threat to global health care and security. Landfills, which are reservoirs for many pharmaceuticals, provide a conducive habitat for antimicrobial-resistant microbes and resistant gene transfer and are therefore a major contributor to the phenomenon of antimicrobial resistance. Hence, this study determined the levels of three widely used antibiotics, metronidazole, penicillin, and amoxicillin, and the occurrence of antimicrobial resistance amongst microbes in soil and leachate samples from active and abandoned landfill sites in Kumasi, Ghana. Soil samples were collected from one active and four abandoned landfills, while leachate specimen was collected only from the active landfill. Sonication and solid-phase extraction (SPE) were used for sample preparation, followed by analysis via an HPLC-PDA method. Isolation and characterization of bacteria were done using standard bacteriological techniques. Antibiotic susceptibility testing was determined following the European Committee on Antimicrobial Susceptibility Testing (EUCAST) guidelines. Antibiotics were detected at very high concentrations in the specimen collected from both active and abandoned landfill sites. For leachate samples obtained from Dompoase, penicillin was present at the highest concentration (67.42 ± 5.35  μ g/mL, p < 0.05 ) followed by metronidazole (18.25 ± 7.92  μ g/mL) and amoxicillin (10.96 ± 6.93  μ g/mL). In general, the levels of antibiotics in soil samples were similar at both active and abandoned landfill sites. Nonetheless, as with leachates, penicillin levels were much higher (p < 0.05 ) than levels of amoxicillin and metronidazole within any particular site. When screened against some antibiotics, Enterobacteriaceae and some Bacillus and Listeria species isolated from the soil and leachate samples proved to be resistant. The high levels of antibiotics coupled with the presence of resistant microbes at these landfills sites call for immediate measures to halt the disposal of pharmaceuticals in the environment so as to avert any possible public health setback.